The role of nutrition in childhood asthma - Broberg, Taneli (My University, 2023)
Background: Asthma is a chronic respiratory disease with high prevalence in the Western world. The global burden of asthma continues to increase, especially in low- to middle-income countries due to urbanization. Childhood-onset asthma is typically related to allergy and is often preceded by frequent wheezing. Furthermore, atopic dermatitis, food allergy or allergic rhinitis are common predictors of childhood asthma, as depicted in “atopic march”. Nevertheless, the pathogenesis of asthma consists of numerous factors, including hereditary and environmental components. Early exposure to tobacco smoke, pollution and respiratory infections has already been associated with the development of asthma. Current research aims to identify more modifiable risk factors linked with asthma to develop effective preventive guidelines. Researchers have studied the relationship of specific nutrients or other dietary factors with the risk of developing allergic diseases. These studies focus especially on the first 1000 days of life, including prenatal and postnatal phases. Methods: Database search was performed in PubMed and relevant articles were selected from 2015 to present including a few older studies as well. Randomized controlled trials were prioritized. Search was limited to vitamin D, probiotics, fish oil and processed food. This review focuses on the preventive role of these nutrients related to childhood allergic symptoms, mainly asthma. Results: 16 RCTs were included along with 9 cross-sectional or population-based original studies. Additionally, systematic reviews were used to compare the results. Vitamin D reduced the risk of asthma/wheeze in two studies at 1-3 years, but the effect was not sustained in longer follow-ups. Probiotics were associated with reduced risk of eczema but not with asthma or wheeze. Fish oil supplementation showed mixed results in prevention of childhood asthma or wheeze. Consumption of ultra-processed food increased the risk of childhood asthma or wheeze in majority of reviewed articles although one study reported contrasting results. Conclusions: Currently there is no recommendations concerning dietary changes or supplements made solely for the prevention of childhood asthma. We identified that vitamin D supplementation during pregnancy or infancy might not be effective in long-term prevention of childhood asthma. Probiotics show potential in preventing atopic dermatitis but similar effect is not seen with asthma or wheezing illness. Fish oil supplementation with regular doses might not be effective in prevention of asthma or wheeze. High consumption of ultra-processed foods seems to be associated with childhood respiratory symptoms and asthma with one study reporting non-significant effect.

Tausta: Astma on krooninen hengitysteiden sairaus, jolla on korkea prevalenssi länsimaissa. Astman aiheuttama globaali tautitaakka jatkaa kasvuaan, erityisesti matalan ja keskitason palkkatulon maissa kaupungistumisen vuoksi. Lapsuuden astma on tyypillisesti allergista ja sitä edeltää usein toistuva uloshengityksen vinkuna. Lisäksi atooppinen ihottuma, ruoka-allergiat ja allerginen nuha ovat yleisiä ennusmerkkejä astman kehittymiselle “atooppisen marssin” edetessä. Astman patogeneesi on kuitenkin monitekijäinen, koostuen muun muassa perintö- ja ympäristötekijöistä. Aikainen altistus tupakansavulle, ilmansaasteille ja hengitystieinfektioille on jo osoitettu lisäävän riskiä astman kehittymiselle. Nykyinen tutkimustyö pyrkii selvittämään lisää muunneltavia riskitekijöitä astmalle, jotta voitaisiin kehittää ennaltaehkäiseviä ohjeistuksia. Tutkijat ovat tarkastelleet erilaisten ravintotekijöiden yhteyttä allergisiin sairauksiin, painottaen erityisesti lapsen ensimmäistä tuhatta elinpäivää. Menetelmät: Tietokantahaku suoritettiin PubMedissa, josta valittiin asianmukaiset artikkelit tiivistelmien perusteella vuodesta 2015 eteenpäin. Satunnaistettuja kontrolloituja tutkimuksia priorisoitiin. Haku rajattiin D-vitamiiniin, probiootteihin, kalaöljyyn ja prosessoituun ruokaan. Tämä katsaus keskittyy edellä mainittujen ravintotekijöiden ennaltaehkäisevään rooliin lapsuuden allergisten oireiden ja astman suhteen. Tulokset: Katsaukseen sisällytettiin 16 satunnaistettua kontrolloitua tutkimusta ja 9 havaintotutkimusta. Lisäksi systemaattisia katsauksia käytettiin tulosten vertailuun ja analysointiin. D-vitamiini vähensi astman tai vinkunan riskiä kahdessa tutkimuksessa 1-3 vuoteen asti, mutta vaikutus ei säilynyt pidemmässä seurannassa. Probiootit vähensivät atooppisen ekseeman riskiä, mutta samanlaista vaikutusta ei havaittu astman tai vinkunan suhteen. Kalaöljylisän käytöstä astman ennaltaehkäisyssä on ristiriitaisia tuloksia. Prosessoidun ruoan kulutus lisäsi riskiä lapsuuden astmaan tai toistuvaan vinkunaan useimmissa katsaukseen sisällytetyissä tutkimuksissa. Johtopäätökset: Suosituksia ruokavalion muutosten tai lisäravinteiden suhteen yksinomaan lapsuusiän astman ehkäisyä varten ei ole tehty. Tämän katsauksen perusteella D-vitamiinilisä raskauden tai imeväisiän aikana ei mahdollisesti estä lapsuuden astman kehittymistä myöhemmällä iällä. Probiootit vaikuttavat vähentävän atooppisen ekseeman riskiä, mutta eivät astman. Kalaöljylisän käyttö tavanomaisilla annoksilla ei näytä vähentävän astman ilmaantumista. Prosessoidun ruoan korkea kulutus oli yhteydessä lapsuusiän hengitystieoireisiin ja astmaan.
Keywords: asthma, wheezing, children, prevention, vitamin D, probiotics, fish oil, processed food